Interventions on human capital formation among vulnerable populations: experimental evidence from two large-scale programs in Brazil - Costa, Gabriel Weber (2022)
Essay 1 - We study a large-scale parenting program in the south of Brazil whose goal is to promote the full development of children during the early childhood period. We explore random assignment of eligible families into a treatment and a control group to evaluate program effects on measures of child development, parenting, caregiver mental health and family access to services. Our results suggest that, under regular implementation, the program was effective in improving motor skills of treated children. We also find evidence of improvements in parenting skills and family interactions consistent with program design. Children with caregivers of lower educational backgrounds seem to benefit the most from the intervention. Essay 2 - In this paper, we present evidence on the effects of a comprehensive training program that encompasses general, technical and soft skills, as well as activities related to social participation and citizenship building, under a curriculum of 800 hours of activities. Targeted at youth at-risk, vacancies were assigned randomly to a cohort applying to the program in Rio de Janeiro, allowing for comparability between treatment and control groups. We use administrative data to assess program impacts on formal employment and welfare receipt, and explore primary data related to family formation outcomes. Our results suggest that male beneficiaries experience persistent gains in formal employment, while women have an increased chance of receiving welfare benefits up to ten years after the program. Women with lower educational levels and with no children at the baseline are most affected, the same subgroups that face an increase in fertility after two years following the end of the intervention.